2018
DOI: 10.1049/iet-syb.2018.5026
|View full text |Cite
|
Sign up to set email alerts
|

Study of cohabitation and interconnection effects on normal and leukaemic stem cells dynamics in acute myeloid leukaemia

Abstract: On the basis of recent studies, understanding the intimate relationship between normal and leukaemic stem cells is very important in leukaemia treatment. The authors' aim in this work is to clarify and assess the effect of coexistence and interconnection phenomenon on the healthy and cancerous stem cell dynamics. To this end, they perform the analysis of two time-delayed stem cell models in acute myeloid leukaemia. The first model is based on decoupled healthy and cancerous stem cell populations (i.e. there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…We then used it to elaborate the conditions that are sufficient and necessary for the global asymptotic stability of the positive healthy steady state; knowing its significant meaning from clinical point of view. This result confirms our previous researches [30], [31] and is explained as follows: if we act on the interconnection mechanism modeled by (18), (19) and (20) in a specific way, we may be able to eradicate LSCs and hence reinforce HSCs. The HSCs reinforcement stabilizes pre-leukemic states as introduced in [14].…”
Section: Conclusion and Discusionsupporting
confidence: 91%
“…We then used it to elaborate the conditions that are sufficient and necessary for the global asymptotic stability of the positive healthy steady state; knowing its significant meaning from clinical point of view. This result confirms our previous researches [30], [31] and is explained as follows: if we act on the interconnection mechanism modeled by (18), (19) and (20) in a specific way, we may be able to eradicate LSCs and hence reinforce HSCs. The HSCs reinforcement stabilizes pre-leukemic states as introduced in [14].…”
Section: Conclusion and Discusionsupporting
confidence: 91%
“…Thus, it is possible to understand the therapy mechanism based on this observation. • it is common to mix different therapeutic agents (having different activation mechanisms) [26], [24] in chemotherapy in order to eradicate sick cells or inhibit their proliferation [27], [25]. We verified this well known fact, by showing that the extinction of leukemic cells depends on δ i , G i (0) and β i (0) in Theorem III-A-III-B.…”
Section: Casesupporting
confidence: 61%
“…where ϒ i (t) and ψ i (t) are the functions defined in (22) and (25), respectively. If u i−1 (t) = 0, then its derivative along the trajectories of (9) satisfieṡ…”
Section: Casementioning
confidence: 99%
“…Previous works by Wolfrom et al, (1994, 2000, 2004) [ 23 , 24 , 25 ], Guerroui et al, (2005) [ 26 ] and Laurent et al, (2010) [ 27 ] has investigated the chaotic dynamics of hepatocellular carcinoma cells as well as bone marrow progenitor cells [ 23 ]. In addition, few works have highlighted the oscillatory nature of leukemic cell proliferation [ 28 ]. Finally, in a previous work we have also reported that we have found evidence of deterministic chaos in leukemia cells in vitro [ 29 ].…”
Section: Introductionmentioning
confidence: 99%